Laurie Ruth Johnson (ed.), Germany from the Outside. Rethinking German Cultural History in an Age of Displacement (Altre Modernità, 2023)
Laurie Ruth Johnson (ed.), Germany from the Outside.  Rethinking German Cultural History in an Age of Displacement (New York, Bloomsbury, 2022, 368 pp. ISBN 978-501-375-903) by Alessandra Goggio